Effect of carbon dioxide and bicarbonate as inorganic carbon sources on growth and adaptation of autohydrogenotrophic denitrifying bacteria - Ghafari, S.; Hasan, M.; Aroua, M.K. (Journal of Hazardous Materials, 2009)
Acclimation of autohydrogenotrophic denitrifying bacteria using inorganic carbon source (CO 2 and bicarbonate) and hydrogen gas as electron donor was performed in this study. In this regard, activated sludge was used as the seed source and sequencing batch reactor (SBR) technique was applied for accomplishing the acclimatization. Three distinct strategies in feeding of carbon sources were applied: (I) continuous sparging of CO 2, (II) bicarbonate plus continuous sparging of CO 2, and (III) only bicarbonate. The pH-reducing nature of CO 2 showed an unfavorable impact on denitrification rate; however bicarbonate resulted in a buffered environment in the mixed liquor and provided a suitable mean to maintain the pH in the desirable range of 7-8.2. As a result, bicarbonate as the only carbon source showed a faster adaptation, while carbon dioxide as the only carbon source as well as a complementary carbon source added to bicarbonate resulted in longer acclimation period. Adapted hydrogenotrophic denitrifying bacteria, using bicarbonate and hydrogen gas in the aforementioned pH range, caused denitrification at a rate of 13.33 mg NO 3 —N/g MLVSS/h for degrading 20 and 30 mg NO 3 —N/L and 9.09 mg NO 3 —N/g MLVSS/h for degrading 50 mg NO 3 —N/L.